Elasticity improves handgrip performance and user experience during visuomotor control - Mace,M; Rinne,P; Liardon,J-L; Uhomoibhi,C; Bentley,P; Burdet,E (Royal Society Open Science, 2017)
Passive rehabilitation devices, providing motivation andfeedback, potentially offer an automated and low-cost therapymethod, and can be used as simple human–machine interfaces.Here, we ask whether there is any advantage for a handtrainingdevice to be elastic, as opposed to rigid, in terms ofperformance and preference. To address this question, we havedeveloped a highly sensitive and portable digital handgrip,promoting independent and repetitive rehabilitation of graspfunction based around a novel elastic force and position sensingstructure. A usability study was performed on 66 healthysubjects to assess the effect of elastic versus rigid handgripcontrol during various visuomotor tracking tasks. The resultsindicate that, for tasks relying either on feedforward or onfeedback control, novice users perform significantly betterwith the elastic handgrip, compared with the rigid equivalent(11% relative improvement, 9–14% mean range; p < 0.01).Furthermore, there was a threefold increase in the number ofsubjects who preferred elastic compared with rigid handgripinteraction. Our results suggest that device compliance is animportant design consideration for grip training devices.